Video as a mediating artefact of science learning: Cogenerated views of what helps students learn from watching video - Higgins J; Moeed A; Eden R (Brill, 2018)
“Doing” science in the form of practical work is one pedagogical approach to learning science alongside others such as talking science, writing science, reading science and representing science. However, scientific ideas cannot always be illustrated through practical work or field trips, therefore, different kinds of activities are needed to represent these ideas. This study focused on the power of cogenerative dialogues for teachers to learn about their students and their video preferences for learning science in a secondary science classroom. The analysis of the use of video as a mediating artefact drew on an interpretive approach framed as authentic participant-centered inquiry and employed multiple theoretical frameworks to generate perspectives on the affordances and constraints of learning from video. Through a cogenerative dialogue intervention we found that video could afford the learning of scientific ideas, however, some videographic features were distracting to students and constrained their learning. We argue that video clips as cultural artefacts are inscribed with emotion that structures students’ opportunities to engage with scientific ideas. However, to accept the authoritative information presented in videos as facts uncritically was a missed opportunity to shape students’ epistemological understanding that scientific knowledge is evidence-based and subject to critique. The implications for designing pedagogical approaches that encourage a critical stance to explore the ongoing social construction and communication of scientific ideas are discussed.
© The Author(s). 2018